Implementation and Access Gaps in Infectious Disease Screening for Migrants in Europe: A Structured Review with Thematic Synthesis From the ESGITM Group - Rosa Buonamassa; Nikolaos Markou-Pappas; Alberto Matteelli; Ferenc Balázs Farkas; Muhammad Asaduzzaman; Luisa Frallonardo; Botond Lakatos; Annalisa Saracino; Alba Cuxart-Graell; Nathan Bertelsen; Christian Wejse; Alexandre Raphael Meduri; et al. (Annals of Global Health, 2026)
Background: Infectious disease screening is widely recommended for migrants in Europe, yet implementation remains inconsistent across countries and settings. While guidance has focused on which infections to screen for, less attention has been paid to how screening is delivered, accessed, and linked to care. This structured review with thematic synthesis aimed to synthesize evidence on implementation gaps, barriers, and facilitators, with particular attention to differences across the migratory cycle. Methods: A structured search was conducted across PubMed, Scopus, Web of Science, and Google Scholar for publications from January 2000 to February 2026, addressing infectious disease screening or related migrant health assessments in European settings. Of 49 included publications, 13 empirical studies formed the primary analytical basis and were quality‑appraised using the Mixed Methods Appraisal Tool (MMAT, 2018); the remaining 36 contextualizing publications were used to interpret findings. Eligibility screening was performed independently by two reviewers. Results: Six interconnected thematic domains shaped screening implementation: administrative and legal barriers; communication, language, and cultural mediation; trust, stigma, and perceived coercion; organizational capacity and fragmented care pathways; the role of NGOs and community actors; and contextual differences across the migratory cycle. Barriers varied across the screening‑to‑care cascade: communication barriers and mistrust primarily affected uptake; legal and organizational barriers constrained linkage to diagnosis and treatment; and legal instability and fragmented services undermined continuity of care. First‑arrival settings were characterized by systematic screening and high service pressure; long‑term settlement contexts relied more heavily on primary care capacity, trust, and legal entitlement. Conclusions: Implementation gaps are driven less by the absence of clinical guidance than by structural, organizational, and relational barriers limiting access, linkage, and continuity. Screening should be embedded within integrated, migrant‑centered care pathways supported by cultural mediation, trusted community actors, and separation from immigration enforcement.